JEJARING MUHAMMADIYAH (Sebuah Analisis Recovery Bencana Merapi Yang Dilakukan Organisasi Muhammadiyah) - Al Akbar, Nuruddin (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2012)
This article is based on the research conducted by the writer in Desember 2010 until January 2011. The objective of the research is to know: 1) How was Muhammadiyah as an Islamic social organization involved in handling the recovery program (post Merapi eruption) in 2010. 2.) How was Muhammadiyah used it’s network in the recovery program. The research belongs to case study. The research employed two techniques to collect the data; 1.) interview, and 2.) overview. After the data was gathered, the data was analyzed by the descriptive qualitative techniques. Some of the important search findings can be stated as follow: 1.) Muhammadiyah as an Islamic social organization was actively involved in the recovery program at post Merapi eruption by delivering human resources and material resources. 2.) Muhammadiyah created MDMC (Muhammadiyah Disaster Management Centre) to optimize or maximize the effect of handling the recovery program. Kata Kunci : Muhammadiyah, recovery, network